A Comparison of Unidimensionality and Measurement Precision of the Narcissistic Personality Inventory and the Narcissistic Admiration and Rivalry Questionnaire. (March 2019) - Grosz, Michael P.; Emons, Wilco H. M.; Wetzel, Eunike; Leckelt, Marius; Chopik, William J.; Rose, Norman; Back, Mitja D.
The current study compares the closeness to unidimensionality (CU) and measurement precision (MP) of the Narcissistic Personality Inventory (NPI)—with either a pairwise forced-choice or 5-point Likert-type scale response format—to the Narcissistic Admiration and Rivalry Questionnaire (NARQ). Minimum rank factor analysis and item information curves from item response models were utilized. The results mainly confirmed our expectations that NPI subscales are lower in CU and MP compared with NARQ subscales when the NPI was administered with its traditional forced-choice response format. When the NPI was administered with a 5-point Likert-type scale response format, the NPI subscale Leadership/Authority and NPI Grandiose Exhibitionism showed similarly high levels of CU and MP as the two NARQ subscales. While the NPI subscale Entitlement/Exploitativeness had a higher CU than the NARQ subscales it showed considerably lower levels of MP.